Benjamin Thompson-- Count Rumford : Count Rumford on the nature of heat - Brown, Sanborn C. (Sanborn Conner), 1913-1981 (Men of physics., 1967)
Men of Physics: Benjamin Thompsona₄Count Rumford: Count Rumford on the Nature of Heat presents the life and works of Count Rumford, an American-born British physicist and inventor. This book is divided in two parts. The first part gives a biographical sketch of Count Rumford, Benjamin Thompson, who was born on March 23, 1753 and died in 1814. This part also discusses the contemporary caloric theory and the reason why Rumford disbelieved the theory. The second part presents his technical works, discoveries, and contributions in the field of physics. Some of which are his demonstration of the e.